Artificial intelligence and the library environment: theoretical and practical aspects (Bibliouniversitas@ABRM.md, 2025)
Artificial intelligence (AI) is significantly transforming the library environment, having a profound impact on the way libraries carry out their activities and serve their users. This paper explores both the theoretical and practical aspects of integrating AI into librarianship. It highlights the evolution of AI technologies and how they contribute to the optimization of internal processes, improving the accessibility and quality of information services. It also discusses ways in which libraries can adopt innovative solutions, such as chatbots and semantic search systems, to more effectively respond to user needs. The study emphasizes the importance of a proactive approach in the adoption of AI, promoting the need for continuous training of staff to fully capitalize on the potential of this technology. In conclusion, strategies for integrating AI into library activities are proposed, highlighting that although technology can automate certain processes, human interaction remains essential, thus ensuring an experience repertory between tradition and innovation in the contemporary library landscape.
Keywords: social media; artificial intelligence; digital marketing; librarianship